Peziarahan Bima Mencari Air Kehidupan - Hardono Hardono (Jurnal Orientasi Baru, 2015)
Water is the source of life. Every living thing depends on the presence of water. Without water, life will never exist. Physically, water is needed by every of the absolute water has its own meaning. Man pulls out spiritual meaning of the local cultures value especially about Wayang story. The meaning is Peziarahan Bima Mencari Air Kehidupan Dewaruci. Bima is a fictional character in Wayang culture that developed in Java. Bima is a symbol of man who longs to live with God. Bima integrates his existence and essence of his life. Bima is a true image of all human pilgrimage in the world. Bima is a symbol of individuation to achieve the perfection of life. Perfection was reflected in Acts Dewaruci. Bima met Dewaruci, and received Eternal Life Water (Words of Salvation). Finally, Bima can live happily in manunggaling kawula Gusti.